In vitro Antimicrobial Effect of Punica granatum Extract versus Chlorhexidine on Streptococcus sobrinus, Streptococcus sanguinis, and Candida albicans - E Tavazo Zadeh; P Aref; N Askarizadeh; F Emadi (Islamic Azad University, 2023)
Background and Aim: Considering the search for an effective antimicrobial agent comparable to chlorhexidine (CHX), this study aimed to assess the antimicrobial effect of Punica granatum (P. granatum) hydroalcoholic extract on Streptococcus sobrinus (S. sobrinus), Streptococcus sanguinis (S. sanguinis) and Candida albicans (C. albicans), in comparison with CHX. Materials and Methods: In this in vitro study, the disc diffusion test was used to assess the antimicrobial activity of the extract by measuring the growth inhibition zones; while, the microdilution and macrodilution broth tests were applied to find the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the extract against the tested microorganisms. The MBC was measured using the blood agar or Mueller Hinton agar culture medium. The Sabouraud dextrose agar culture medium was used for C. albicans. Each test was repeated in triplicate, and data were analyzed by independent samples t-test and Mann-Whitney U test. Results: None of the tested microorganisms showed any resistance to the extract. CHX had the highest antimicrobial effect against all tested microorganisms. The MIC of the hydroalcoholic extract of P. granatum was 2.5 mg/mL for S. sobrinus and S. sanguinis, and 5 mg/mL for C. albicans. Its MBC was 5 mg/mL for S. sobrinus and S. sanguinis, and 10 mg/mL for C. albicans. The mean diameter of the growth inhibition zone for S. sobrinus caused by CHX was significantly greater than that caused by P. granatum extract (Mann-Whitney U test, P=0.043). The same result was obtained for S. sanguinis (Student sample t-test, P=0.002), and C. albicans (Mann-Whitney U test, P=0.046). Conclusion: The hydroalcoholic extract of P. granatum has bacteriostatic and bactericidal effects on S. sanguinis and S. sobrinus and antifungal effect on C. albicans comparable to CHX.